(untitled) (Revista de Ciências Agroveterinárias, 2020)
Isoxaflutole (IFT) is a pre-emergence herbicide used to control of a wide range of broadleaf and grass weeds, especially those resistant to other herbicide classes, such as glyphosate and atrazine. Although its herbicidal potential was identified in the early 90’s, IFT is still a new active ingredient in Brazil and little is known about its effects, mainly regarding to ecotoxicity of formulated products to soil macro and mesofauna groups. This study aimed to assess behavioral, acute, and chronical effects (avoidance, lethality, and reproduction) of the commercial product ProvenceTM 750 WG (750 g a.i. L-1 isoxaflutole) on the test organisms Eisenia andrei (earthworms) and Folsomia candida (collembolans) using standardized ISO guidelines. The results showed the avoidance of the earthworm species only at >300 times the predicted field doses, as well as a decrease in reproduction over >150 times the predicted field dose. Neither the avoidance, nor lethality or reproduction response were found for the collembolan species. The laboratory results showed that it is possible to assume that ProvenceTM is not toxic to earthworms and collembolans, even at the highest field dose applied, ensuring the safety of soil communities.